(untitled) (Journal of Oriental Studies, 2017)
When teaching a foreign language to use different techniques – it increases the interest of the student. Therefore, a new training requirements emerge and new teaching methods. These methods teachers should effectively use. Therefore, this article deals with the problems of research methods training, explores new methods of teaching Chinese language, examples are given.